2022
DOI: 10.1021/acsanm.2c02207
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up De Novo Synthesis of Porous Organic Polymers with Enone Functionalities as Supports for Pd and Cu Nanoparticles for Catalytic Tandem Synthesis

Abstract: Two porous organic polymers (POPs), namely, ANT and NAP based on N,N,N′,N′-tetrakis(4-acetylphenyl)anthracene-9,10-diamine and N,N,N′,N′-tetrakis(4acetylphenyl)naphthalene-1,4-diamine, respectively, as core scaffolds and enone functionalities as the connecting backbones, were synthesized using an aldol condensation reaction. The enone backbones of the POPs mimic α,β-unsaturated ketone functionalities of dibenzylideneacetone (dba), which is frequently employed to stabilize Pd(0), e.g., Pd 2 (dba) 3 , for effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Tandem reaction catalyzed by Cu and Pd based POPs. [54] the heterogeneous catalyst development. This understanding not only helps in the improvement of catalyst performance but also indicates the role of other physical parameters such as porosity, surface area, surface wettability, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tandem reaction catalyzed by Cu and Pd based POPs. [54] the heterogeneous catalyst development. This understanding not only helps in the improvement of catalyst performance but also indicates the role of other physical parameters such as porosity, surface area, surface wettability, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Tandem reactions Yadav et al reported the use of enone functionalities in POP as support for metal nanoparticles (Pd, and Cu). [54] Two different porous organic polymers were synthesized via aldol condensation between an aromatic tetraketone and aromatic dialdehyde, as a result, α,β-unsaturated enone functionalities were produced. These enone functionalities were used to stabilize metal nanoparticles (Pd, and Cu) named Pd@ANT, Pd@NAP, Cu@ANT, and Cu@NAP.…”
Section: Oxidation Of Primary and Secondary Alcoholsmentioning
confidence: 99%
“…In our ongoing research focused on the development of metal–organic frameworks (MOFs) , and POPs , by bottom-up de novo design of building blocks, we have demonstrated the development of POPs as heterogeneous recyclable catalysts for organic transformations. In our recent work, we showed that dialkyl bipyridine-based ionic POPs (IPOPs) can be exploited for Michael additions and condensation reactions; dialkyl salts of 4,4′-bipyridines are commonly known as viologens (paraquats) and serve as effective electron acceptors in photoinduced electron transfer reactions .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] In general, the performances of catalytic materials are controlled by the kind of support employed, the porous structure and physiochemical properties. In our continuing investigations on porous MOFs [27][28][29][30][31] and POPs, [32][33][34] we specifically sought to explore the catalytic performances of POPs endowed with carboxy functionalities. Herein, we report the synthesis of a carboxy-functionalized porous organic polymer, that is, Carboxy-POP, by Friedel-Crafts polyalkylation followed by hydrolysis, and its application for facile catalytic synthesis of biologically-active xanthenes and acridine derivatives.…”
Section: Introductionmentioning
confidence: 99%